Climate-smart agriculture implementation evidence in Ghana: Supporting scaling strategies for enhanced resilience in Ghana - Mponela, Powell; Dziwornu, Michael Gameli; Agyarko-Fosu, Fred; Inusah, Sandra; Odonkor, Ezekiel Narh; Sackey, Tracy Adjeley; Mamah, Samiratu Abdulai; Akpatsu, Isaac Boatey (2023)
Agriculture remains crucial to Ghana’s economy, livelihoods and food security, contributing 20.3% of GDP in 2015. However, climate change creates mounting pressures on agricultural productivity and sustainability nationwide. Ghana has experienced rising temperatures, increased variability in rainfall, and more extreme weather events over the past decades. Climate shocks undermine crop and livestock yields, raise production risks and costs, lower incomes, and exacerbate hunger and poverty levels for smallholder farmers. In response systematic adaptation and mitigation strategies have been mainstreamed across Ghana’s agricultural sector in the form of Climate-smart agricultural practices